INDIVIDUAL CORRELATION OF OXYGEN DELIVERY WITH HAEMOGLOBIN LEVEL IN 20-YEAR-OLD WOMAN WITH HB 1.8 WITH INCOMPATIBLE CROSS-MATCH RESULTS: CASE REPORT STUDY - Permana, Septian Adi; Yuliana, Friskha (Rumah Sakit Umum Daerah Dr. Moewardi, 2023)
BACKGROUND Clinical assessment of the delivery of tissue oxygenation is very challenging for clinicians to study. Anaemia reflects a decrease in oxygen carrying capacity in the blood which is very at risk of oxygen delivery (DO2) insufficiency and cellular hypoxemia, to assess tissue hypoxia in addition to being a reliable tool, the clinician must also adjust to the patient's clinical and hemodynamic. Blood transfusions are generally used to correct anaemia precisely and efficiently, but in certain circumstances that make it impossible for clinicians to perform blood transfusions, at that time we have to think of other methods of therapy in patients. METHODS 20-year-old woman came with anaemia, with a haemoglobin (Hb) level of 6.0 g/dl, a stable clinical condition and hemodynamic within normal limits, a blood transfusion was planned but the results of the Comb test was incompatible, so it was an absolute contraindication for transfusion. The patient experienced clinical changes that indicated the occurrence of tissue hypoxia when the Hb level was 2.0gr/dl. The clinician decided to maximize DO2, and reduce oxygen demand/consumption (VO2), so that there is a balance. The patient was treated with steroids, suspected autoimmune haemolytic anaemia (AIHA). On the eighth day of clinical treatment the patient improved, hemodynamically stable, and Hb increased. CONCLUSION Clinical valuation of the distribution of tissue oxygenation is very important for AIHA patient.